1993
DOI: 10.1523/jneurosci.13-03-01022.1993
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of lateral line sensory organs during tail regeneration in salamanders: identification of progenitor cells and analysis of leukocyte activity

Abstract: It has been proposed that supporting cells may be the progenitors of regenerated hair cells that contribute to recovery of hearing in birds, but regeneration is difficult to visualize in the ear, because it occurs deep in the skull. Hair cells and supporting cells that are comparable to those in the ear are present in lateral line neuromasts, and in axolotl salamanders these cells are accessible to microscopic observation in vivo. After amputation of a segment of the tail that contains neuromasts, cells from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 45 publications
3
65
1
Order By: Relevance
“…This hypothesis is supported by the fact that the timing and degree of cell division we detected in our cultures closely resemble those seen in vivo after a single injection of gentamicin or noise damage (Stone and Cotanche, 1994;Bhave et al, 1995). Although the proliferative capacity of support cells has not been determined, studies have shown that support cells are able to divide more than once after hair cell loss (Jones and Corwin, 1993;Stone and Cotanche, 1994;Presson, 1995).…”
Section: Progenitor Cells In Culturessupporting
confidence: 73%
“…This hypothesis is supported by the fact that the timing and degree of cell division we detected in our cultures closely resemble those seen in vivo after a single injection of gentamicin or noise damage (Stone and Cotanche, 1994;Bhave et al, 1995). Although the proliferative capacity of support cells has not been determined, studies have shown that support cells are able to divide more than once after hair cell loss (Jones and Corwin, 1993;Stone and Cotanche, 1994;Presson, 1995).…”
Section: Progenitor Cells In Culturessupporting
confidence: 73%
“…In the nervous system, stem cells give rise to proliferating progenitors called transient amplifying cells, the progeny of which then differentiate (Alvarez-Buylla et al, 2001;Doetsch, 2003). In this study, we provide evidence for two distinct subpopulations of proliferating neuromast cells, designated as internal and peripheral SCs (Jones and Corwin, 1993;Williams and Holder, 2000). We suggest that internal SCs act as transient amplifying cells that give rise to new HCs during regeneration, whereas peripheral SCs may include a dedicated population of progenitor cells responsible for renewing the internal SC population.…”
Section: Two Subpopulations Of Proliferating Cells Have Separate Funcmentioning
confidence: 61%
“…With the aid of the SYTOX nuclear counterstain, BrdU-positive cells in three neuromasts (MI1, O1, and OP1) were subdivided as either internal or peripheral SCs based on their position within the neuromast (Fig. 2 D) (Jones and Corwin, 1993;Williams and Holder, 2000). Internal SCs are centrally located within the neuromast, whereas peripheral SCs lie along the periphery.…”
Section: Two Separate Subpopulations Of Support Cells Exist Within Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The medial cerebral cortex of lizards, which resembles the dentate gyrus of mammals, undergoes postnatal neurogenesis and can regenerate in response to injury (Lopez-Garcia et al 1992). Newts can regenerate their tails, limbs, jaws, and ocular tissues, and the neurons that occupy these regions (Jones and Corwin 1993;Brockes 1997). Goldfish undergo retinal neurogenesis throughout life (Johns and Easter 1977) and, impressively, can regenerate surgically excised portions of their retina in adulthood (Hitchcock et al 1992).…”
Section: Functional Adult Neurogenesis Occurs In Non-mammalian Vertebmentioning
confidence: 99%